Retinal vascular pathology in a mouse model of Lafora progressive myoclonus epilepsy - Ruchira Pranay Patil; Nitin Kumar; Arveen Kaur; Rajendra Kumar Munian; Bishakh Bhattacharya; Subramaniam Ganesh; Rashmi Parihar (Neuroscience Research)
Neurodegenerative diseases (ND) affect distinct populations of neurons and manifest various clinical and pathological symptoms. A subset of ND prognoses has been linked to vascular risk factors. Consequently, the current study investigated retinal vascular abnormalities in a murine model of Lafora neurodegenerative disease (LD), a fatal and genetic form of progressive myoclonus epilepsy that affects children. Here, arterial rigidity was evaluated by measuring pulse wave velocity and vasculature deformations in the retina. Our findings in the LD mouse model indicate altered pulse wave velocity, retinal vascular thinning, and convoluted retinal arteries.